Syntheses of variants of π(σ) aromatic modified N-methyl N-confused porphyrinoids with adaptive properties - Panua, Anirban; Velmurugan, Gunasekaran; Comba, Peter; Rath, Harapriya (Chemistry, 2025)
Retrosynthetically designed and syntheses of three unprecedented core modified N-confused porphyrinoids exhibiting vis-NIR absorption with tunable aromaticity is reported. Controlled modification of types of oxidants (chloranil vs. DDQ) has led to the isolation of 18π-aromatic porphyrinoid 7 (upon chloranil oxidation) while DDQ oxidation has led to 18 e σ-aromatic porphyrinoids 8 and 9. All the three SN3 hybrid N-confused porphyrinoids 7-9 have been thoroughly characterized via solution state spectroscopic measurements and in-depth DFT studies for concluding π-aromaticity of 7 and σ-aromaticity of 8 and 9. While 7 could recognize the fluoride anion with high selectivity via deprotonation rather than an anion recognition based mechanism, acetate anion binding studies clearly revealed NH⋅⋅⋅AcO− H-bonding interaction in the host-guest complex [7-AcO−] supporting an anion recognition based mechanism. Porphyrinoids 8 and 9 remain unsusceptible to anion recognition. The conformational preorganization and anion induced deprotonation leading to conformational reorganization have been extensively studied by solution state spectroscopic techniques and in depth DFT level theoretical calculations.